The Influence of Investment Knowledge, Capital Market Training, Minimal Capital, Technological Developments, and Motivation on Students' Interest in Investing in the Capital Market - Muhamad Yudi Abni; Rina Trisnawati (Journal of Social Research, 2022)
Background: The younger generation plays an important role in the world of technological development, especially in the field of investment, which is also developing. As evidenced by the number of applications or stock buying and selling sites that continue to appear. Objective: This study aims to determine the influence of Investment Knowledge, Capital Market Training, Minimal Capital, Technological Development, and Motivation on Investment Interest in students of the Muhammadiyah University of Surakarta. The population of this study was 3,525 students and a sample of 100 students with Engineering was obtained. Method: The method used in this study is quantitative. The analysis method used in this study is multiple linear regression analysis. Result: The results of this study prove that the variables of Investast Knowledge, Minimal Capital, and Motivation have a positive and significant influence on investment interest. The Capital Market Training variable has no positive effect and the Technology Development variable has a negative and significant influence on investment interest. Conclusion: The results of this study can be concluded that Investment Knowledge, Minimal Capital, Technological Development, and Motivation affect Investment Interest, while Capital Market Training does not affect Investment Interest.